Peran Orang Tua Dalam Mendukung Prestasi Olahraga Renang Di Hasics Swimming Club Bojonegoro - Rino Faturahman; Made Pramono; Muhammad Dzul Fikri; Joesoef Roepajadi (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
This study aims to determine the role of parents in supporting swimming achievements at Hasics Swimming Club Bojonegoro. The research employs a quantitative approach, with a descriptive quantitative research type. The method used is a survey. The population of the study consists of parents/guardians of swimmers at Hasics Swimming Club. The sampling technique used is total sampling of the parents/guardians who were present during swim practice at Hasics Swimming Club, totaling 30 people.Instruments used include questionnaires and documentation. Data analysis is conducted using descriptive percentage. The results of the study indicate that parental involvement in supporting the swimming achievements at Hasics Swimming Club shows that 3% fall into the "very low" category, 34% into the "low" category, 13% into the "moderate" category, 50% into the "good" category, and 0% into the "very good" category. Parental involvement in supporting the swimming achievements at Hasics Swimming Club refers to an average score of 120.1, which falls into the good category.